KEPEMIMPINAN KYAI DALAT MEREVTTALISASI PESANTREN - Jailani, M.Syahran (At-Ta`lim, 2014)
lslamic Boarding School is institute educatirxr d Ham belodunder head a Kyai, either through forma! band and abo nqr formal with aim to study and practice teaching of idam pass/through study of book turn yellow by emphasizing retgirrsmoral as guidance in have my me to all day long santi. Of somuch many leadership style ( style leadership) which in tellirB byall is expert, but is most of and popular of serig in debate and inmaking reference by all researcher and practitioner only four leadership style, that is: otokrastis, democratic, faires laisser the (free-style), and situasional. Kyai as leader of pesantren in guidingall vinicity society or santri wear approach of situasional. This matter Look in interaction [among/between] Kyai and its its his in educating, teaching book, and give advice, also as consultancyplace of is problem of, so that a Kyai sometime function also as a old at the same time teacher which can meet infinitely of time. Condition of like this visua! that Ieadership of Kyai of[is full (of)responsibility, all ones ear, powerful draw and very is having an effect on. Behavioral thereby kiai can perceive, to be followed the example of, and meant by all its follower derect interaction all daylong.